النسق الديني والاجتماعي والحضور الأنثوي في رواية "وادي الحناء" لجميلة طلباوي - عوادي، يسمينة; بن بردي، اسماء; فتح الله، اسماء; زبدي، منى (University of Eloued جامعة الوادي, 2024)
- الملخص: يهدف هذا البحث الى دراسة النسق الديني والاجتماعي والحضور الأنثوي في رواية وادي الحناء لجميلة طلباوي، التي احتوت ثماني ورقات تسرد أحداث قصة"عويشة" المرأة الصحراوية المثقفة المتحدِّية لعادات وتقاليد مجتمعها الصحراوي المحافظ، كما سلطت الضوء على الزَّاوية ومكانتها في الجنوب الجزائري إضافة إلى عادات وتقاليد وطقوس مجتمع " تيمي" وتعتمد هذه الدراسة على آليات النقد الثقافي، الذي يكشف الأنساق الثقافية و للوصول إلى الهدف المرجو، تمّ اتباع الخطّة المكوّنة من: مدخل يتضمن مفاهيم متعلقة بالنقد الثقافي والنسق الثقافي وفصلين: الأول: الأنساق الثقافية في بعض الروايات (نماذج)، والفصل الثاني: كان تطبيقا على الرواية، تطرّقنا فيه إلى الكشف عن الأنساق الثقافية- تحديدا- النّسق الديني والهيمنة الناعمة والنسق الاجتماعي، وختمنا بحثنا بخاتمة شملت أهم النتائج المتوصل إليها. • Abstract : The research aims to study the religious, social systems and the feminin presence in the novel of « Ouadi El-Henna" which_contains of eight (8) pages narrating the events of the Saharia cultivated woman. «Awicha» who confront her social customs and traditions. Moreover, the novel spots the light on «Zawya» and its status in the South of Algeria, in addition to the customs, traditions and rituals of «Timy» community. the study is based on the cultural critic techniques that reveals the cultural system of a given literary work. To attain these goals, the research goes on the following work plan: starts with an entry to list the notions linked to the cultural critic and system. Besides to two other chapters. The first chapter deals with examples of the cultural system in some novel works. The second chapter: application of the study the novel " Ouadi El Henna" to reveal the cultural systems, mainly the smooth religious and social systems On conclusion, listing the most prominent results.
813/ 017
Keywords: وادي الحناء _ النقد الثقافي _ الأنساق الثقافية; Ouadi El-Henna - the cultural critic - the cultural systems